'Minoritisation' of the other: the Iranian ethno-theocratic state's assimilatory strategies. Issue 1 (2nd January 2021) - Mohammadpour, Ahmad; Soleimani, Kamal
ABSTRACT: Since the establishment of the modern nation-state in Iran in the early twentieth century, the state has viewed Kurds and their political struggle for survival as an existential threat to its integrity. The Islamic Republic's coming to power – after the 1979 Revolution – gravely intensified the state's securitisation policies in the Eastern Kurdistan (also known as Rojhelat). This article, thus, investigates the Islamic Republic's anti-Kurdish strategies starting immediately after the Revolution. Those policies can be best characterised as an exclusionary inclusion. In this liminal sphere of political life, Kurds are subjugated to the daily struggle of preservation of their identity. This paper casts light on the state's assimilatory strategies in Eastern Kurdistan exerted through militarisation, minoritisation, and a steady cultural and demographic transformation of the region.